Utilization of Mean Platelet Volume for Predicting Ischemic Heart Disease in Diabetic and Non-Diabetic Patients - Arefnia, Maryam; Hosseinnezhad Ariani, Toktam; Ghodsirad, Mohammadali; Alirezaei, Toktam; Hosseinzadeh, Elinaz; Amoui, Mahesti; Pirayesh, Elaheh; Norouzi, Ghazaal (Novelty in Biomedicine, 2025)
Background: This study aimed to evaluate the relationship between mean platelet volume (MPV) and myocardial perfusion abnormalities in patients with and without Type 2 diabetes mellitus (DM) using myocardial perfusion scans. Materials and Methods: This cross-sectional study compared 49 patients with Type 2 DM without overt cardiovascular symptoms with 49 healthy controls. Both groups underwent myocardial perfusion scans at rest and under stress conditions. Risk factors were assessed and recorded using a special research-made questionnaire. A complete blood count and MPV results were obtained using the Sysmex - KX-21 system. Data were analyzed using SPSS, with a p-value below 0.05 considered statistically significant. Results: No significant differences were observed between the two groups in terms of Summed Stress Score (SSS), Summed Rest Score (SRS), Summed Difference Score (SDS), Ejection Fraction (EF), and End Systolic Volume (ESV). The only marked variance was a higher average platelet count in the control group. Regression analysis revealed that a one-unit increase in MPV correlated with a 0.46 average increase in SRS in the control group (CI: 0.08-0.83, β: 0.46). Conclusion: MPV may serve as a predictive marker for myocardial perfusion abnormalities, especially in individuals without diabetes. This simple metric could act as an early indicator for coronary artery disease.